The Gender of Precarious Employment in Canada - Cranford, Cynthia; Vosko, Leah; Zukewich, Nancy (Relations industrielles / Industrial Relations, 2003)
SummaryThis article examines the relationship between gender, forms of employment and dimensions of precarious employment in Canada, using data from the Labour Force Survey and the General Social Survey. Full-time permanent wage work decreased for both women and men between 1989 and 2001, but women remain more likely to be employed in part-time and temporary wage work as compared to men. Layering forms of wage work with indicators of regulatory protection, control and income results in a continuum with full-time permanent employees as the least precarious followed by full-time temporary, part-time permanent and then part-time temporary employees as the most precarious. The continuum is gendered through both inequalities between full-time permanent women and men and convergence in precariousness among part-time and temporary women and men. These findings reflect a feminization of employment norms characterized by both continuity and change in the social relations of gender.